Controller and actuator of three independent DC motors In closed loop - Lopes, Gil (2010)
This article describes a solution for a high power controller and actuator of three DC motors in closed loop. This controller can be applied to omnidirectional platform solutions using three motorised Swedish wheels as used by several RobCup MSL robots and Minho omnidirectional Wheelchair. Some existing controllers in the market are reviewed pointing out their characteristics and comparing them with the proposed solution. Operational characteristics and developed algorithms of the proposed system are fully disclosed.